1987
DOI: 10.1021/jm00393a024
|View full text |Cite
|
Sign up to set email alerts
|

6-Methylergoline-8-carboxylic acid esters as serotonin antagonists: N1-substituent effects on 5HT2 receptor affinity

Abstract: Three series of 6-methylergoline-8-carboxylic acid esters with various alkyl substituents in the N1-position were prepared and their 5HT2 receptor affinities measured. Some overlap occurred in the 5HT2 receptor affinities of the different ester series, indicating that both the ester side chain and the indole substituent influenced 5HT2 receptor affinity. While 5HT2 receptor affinity was affected by the structure of the ester side chain, the N1-substituent played a more crucial role in determining 5HT2 receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 1 publication
1
17
0
Order By: Relevance
“…5 To increase solubility of 9,10-dihydrolysergic acid (2) in organic solvents, the corresponding methyl ester 5 was prepared (Scheme 2). 6 In the next steps allylic substituent on 6-N of 5 had to be introduced. To introduce the allylic substituent on 6-N of 5, 9,10-dihydrolysergic acid (2) had to be N-demethylated rst.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 To increase solubility of 9,10-dihydrolysergic acid (2) in organic solvents, the corresponding methyl ester 5 was prepared (Scheme 2). 6 In the next steps allylic substituent on 6-N of 5 had to be introduced. To introduce the allylic substituent on 6-N of 5, 9,10-dihydrolysergic acid (2) had to be N-demethylated rst.…”
Section: Resultsmentioning
confidence: 99%
“…Suspension formed, was stirred at room temperature for 2 h, aer which it was ltered, washed with H 2 O and dried to give titled compound as an off white solid (6. 25 (6). To an oven dried glassware, dried compound 5 (8.51 g, 29.9 mmol) was weighed and anhydrous DCM (200 mL) was added under N 2 atmosphere.…”
Section: Methylmentioning
confidence: 99%
“…Chemistry LY53857 is the prototype in a series of 6-methylergoline-8b-carboxylic acid esters (Marzoni et al 1987;Garbrecht et al 1988) that shows potent 5-HT 2A receptor antagonist activity (Cohen et al 1983). We intended to synthesize structurally related O-acylated derivatives of 9,10-didehydro-8b-hydroxymethyl-6-methylergoline (lysergol) and O-ACYLATED DERIVATIVES OF LYSERGOL AND DIHYDROLYSERGOL-I 8b-hydroxymethyl-6-methylergoline (dihydrolysergol-I), so-called ergoline reverse esters, which share with LY53857 an isopropyl substituent at N(1) and an aliphatic branched-chain substituent at the C-8b position.…”
Section: Resultsmentioning
confidence: 99%
“…Previous in vitro studies using rat tissues showed markedly lower 5-HT, receptor affinity of the desisopropyl ergolines (see Fig. 1 for structures) relative to isopropyl ergolines [ Marzoni et al, 1987;Misner et al, 19901 to a greater extent than would have been predicted based on data generated using the rat 5-€IT, receptor. 5-HT, receptor antagonists have been shown to possess efficacy in animal models of thrombosis [Ashton et al, 1986[Ashton et al, , 1989Bush, 1987;Wilson et a]., 1991;Cohen et al, 1992;Herbert et al, 1993;Cushing et a]., 19931.…”
Section: Introductionmentioning
confidence: 80%
“…Efficacy of these ergolines in rabbit models of thrombosis may be due to the importance of serotonin as a mediator of platelet aggregation in this species [Killani et al, 19911. The present study was designed to compare systematically the effects of amesergide and LY215840 on rabbit platelet aggregation responses to serotonin, both in vitro and ex vivo. Further, we questioned whether the desisopropyl metabolites of amesergide and LY215840 were also antagonists of platelet 5-HT, receptors in the rabbit as has been reported at the human [Nelson et al, 19931 but riot rat [Marzoni et al, 1987;Misner et al, 19901 5-HT2 receptor.…”
Section: Introductionmentioning
confidence: 99%